The effect of platelet-rich fibrin and low-level laser therapy associated with simplified papilla preservation flaps in the management of supra-alveolar periodontal defects = El efecto de la terapia con láser de baja intensidad y fibrina rica en plaquetas asociada con colgajos de preservación de papila simplificados en el tratamiento de defectos periodontales supraalveolares - Subramanian, Sangeetha
The current study aimed to evaluate and compare the effect of Platelet Rich Fibrin (PRF) and Low-Level Laser Therapy (LLLT) on the clinical outcomes when supraalveolar defects were accessed with Simplified Papilla Preservation Flap (SPPF). Forty-five patients presenting with supra-alveolar defects were allocated into three study groups with 15 patients in each group. SPPF approach was performed in each group with the addition of PRF and LLLT in the test groups. In all the study groups, a significant reduction in pocket depth was observed (P<0.001) at 6 months after therapy. The Relative Attachment Gain was significantly higher in the PRF Group (P<0.001) and in the Control Group (P=0.02) at six months compared to baseline. The study groups failed to show significant differences between them when clinical parameters were compared at six months.